Analisis Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Kepuasan Konsumen Dalam Pembelian Roti Ganeca Terhadap Loyalitas Konsumen Di Wirosari - Wulansari, Fitriana; , Drs. M. Nasir, MM (2017)
The pursose of this study was to analyze the effect of service quality product quality and customer satisfaction in the purchase of bread ganeca on consumer loyalty in Wirosari. The method used in this study is quantitative research and primary data. Population in this study is the consumers who buy products from bread ganeca in temtory Wirosari a mount up 40 respondens. Research used validity test with method correlation bivariate pearson, reliability test with category coefficient reliability, assumption test classic (normality test, multikolinearitas test, heteroskedastisitas test). Anality regressive linier multiple, and hypothesis test (test t, test f, and coefficient determinan R2).Based on the analysis about of the effect product quality service quality and customers satisfaction to loyalty customers of bread ganeca in Wirosari. Variable product quality effect significant to customers loyalty. Variable service quality effect significant to customers loyalty. Variable customers satisfaction effect significant to customers loyalty. Keywoards : product quality, service quality, satisfaction and customers loyalty